Participatory epidemiology in disease surveillance and research - Jost, Christine; Mariner, Jeffrey C.; Roeder, P.L.; Sawitri, E.; MacGregor-Skinner, G.J. (World Organisation for Animal Health, 2007)
Participatory epidemiology is the application of participatory methods to epidemiological research and disease surveillance. It is a proven technique which overcomes many of the limitations of conventional epidemiological methods, and has been used to solve a number of animal health surveillance and research problems. The approach was developed in small-scale, community animal health programmes, and then applied to major international disease control efforts. The Global Rinderpest Eradication Program adopted participatory epidemiology as a surveillance tool for controlling rinderpest. This approach was subsequently used in both rural and urban settings in Africa and Asia, for foot and mouth disease, peste des petits ruminants and highly pathogenic avian influenza. Participatory disease surveillance has made an important contribution towards controlling both rare and common diseases. This paper reviews the principal applications of participatory epidemiology and highlights the lessons learned from field applications. In addition, the authors examine future challenges and consider new areas for research.